2008
DOI: 10.1177/1076029608329578
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Hemostatic Effect of the Medicinal Plant Extract Ankaferd Blood Stopper in Rats Pretreated With Warfarin

Abstract: ABS has in vivo hemostatic actions that may provide a therapeutic potential for the management of patients with deficient primary hemostasis in clinical medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 17 publications
4
83
0
3
Order By: Relevance
“…Numerous studies reported the hemostatic effects of topical ABS in the animals with normal [10,12,14,[16][17][18] and defective hemostasis [15,24], and have set the preclinical stage for the development of this hemostatic product. The effects of ABS on hemostatic parameters have also been searched [2,6,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies reported the hemostatic effects of topical ABS in the animals with normal [10,12,14,[16][17][18] and defective hemostasis [15,24], and have set the preclinical stage for the development of this hemostatic product. The effects of ABS on hemostatic parameters have also been searched [2,6,25].…”
Section: Discussionmentioning
confidence: 99%
“…The hemostatic effects of ABS have been observed in vitro and in vivo [12][13][14][15][16][17][18]. Use of ABS as a hemostatic agent in external hemorrhages and in dental treatment in humans provided the first data showing that ABS was safe and effective in humans [9].…”
Section: Introductionmentioning
confidence: 99%
“…Topical safety of ABS in normal healthy human volunteers was shown in a randomized double-blind cross-over Phase I clinical trial after preclinical animal studies [2][3][4][5][6]. ABS has been approved for local topical applications in external post-surgical and post-dental surgery bleedings in Turkey (www.Ankaferd.com).…”
Section: Introductionmentioning
confidence: 99%
“…The quantity of bleeding was measured as follows; rats were placed individually in a standard plastic restraining cage with the tail allowed to hang out freely, the tip of the tail of each rat was cut (4-5 mm) with a sharp pair of scissors and a stopwatch started immediately, a pre-weighed blotting paper was used to collect all drops of blood that flowed from the site of the inflicted injury, the blotting paper was re-weighed after the appearance of the last drop of blood, the difference in weight of the dry and wet blotting paper was taken as the amount of bleeding (Cipil et al, 2009;Yalcinkaya et al, 2011).…”
Section: Amount Of Bleedingmentioning
confidence: 99%